(untitled) (CIPEEX, 2022)
THIS WORK WAS PRESENTED DURING THE IX CULTURAL EXHIBITION OF THE DENTISTRY COURSE IN THE FORMAT OF A THEATER. €ŒBEFORE THE SEA, EARTH AND SKY WERE CREATED, ALL THINGS HAD AN ASPECT THAT WAS CALLED CHAOS€ (BULFINCH, 2002). IN GREEK MYTHOLOGY, CHAOS IS CONSIDERED THE PRIMORDIAL GOD OF THE UNIVERSE, ACCORDING TO THE NARRATIVE OF THE GREEK POET HESIOD. IN THE DICTIONARY, CHAOS MEANS €ŒMIXTURE OF THINGS AND IDEAS IN TOTAL DISHARMONY, CONFUSION€. €ŒA STATE IN WHICH TOTAL CONFUSION AND DISEQUILIBRIUM PREVAIL; DISORDER, DISORDER, ANARCHY, MESS, CONFUSION, BABEL, TURMOIL, CONFUSION, DISARRAY, DISORDER, OBSCURITY, PANDEMONIUM, DISTURBANCE, DISORDER, MUDDLE.€ FROM ANCIENT GREEK Ï‡Î¬Î¿Ï‚ €ŒDARK ABYSS€. THE WORD "CHAOS" CAN BE DEFINED, PHILOSOPHICALLY, AS A DARK VOID, AN UNFATHOMABLE DEPTH THAT PRECEDES AND PROPITIATES THE GENERATION OF THE WORLD. THE OPPOSITE OF CHAOS IS CLARITY, ORDER, ORGANIZATION, HIERARCHY, ORDERING, ARRANGEMENT, ARRANGEMENT, DISTRIBUTION, POSITION, ORDERING, ARRANGEMENT, SCHEME, STRUCTURING, FORMATION, COMPOSITION, PLACEMENT, CONFORMATION, ARRANGEMENT, LAYOUT, AND METHOD. IS THERE AN ORGANIZATION IN CHAOS? IS THERE ORDER IN CHAOS? OR IS CHAOS JUST HERE TO CAUSE?